Voices from captivity: incarceration from Siberia to Guantánamo Bay - Thomas, James E. (Jessica Kingsley Publishers, 2018)
Introduction -- On being locked up -- Settling down -- A community? -- Dealing with the staff -- Prisoners in authority -- The world of communication -- The studied organisation of cruelty -- Cruel and unusual punishment -- Sex and the captive -- Political prisoners -- On freedom -- Bibliography